Predictive Relevance of Ethical Leadership, Quality of Work Life, and Organisational Commitment: Lessons for Leaders - Ampomah, Robert (European Journal of Human Resource, 2025)
Purpose: The study examined ethical leadership, quality of work life, and organisational commitment in colleges of education in Ghana. The main purpose was to assess whether ethical leadership of principals predicted the quality of work life and organisational commitment of tutors. Two hypotheses were generated based on the objectives to guide the study. Materials and Methods: The quantitative cross-sectional design was used in this study. Three hundred and fifty tutors were selected using multistage sampling procedure. Three set of questionnaires were used to elicit responses from participants. Multivariate Multiple Regression and Structural Equation Modelling (SEM) were the statistical tools used to analyse the data gathered. Findings: The findings of the study indicated among others that the sub-dimensions of ethical leadership (communicative ethics, climatic ethics, and behavioural ethics) were not predictors of sub-dimensions of the quality of work life. However, ethics in decision-making a sub-dimension of ethical leadership was a substantial predictor of relationship and cooperation and training and development a sub-dimension of quality of work life. The findings again showed that the sub-dimensions of ethical leadership (communicative ethics, climatic ethics, and behavioural ethics) were not predictors of sub-dimensions of organisational commitment. However, ethics in decision-making a sub-dimension of ethical leadership was a substantial predictor of continuance commitment a sub-dimension of organisational commitment. The findings were discussed in relation to the literature. Unique Contributions to Theory Policy and Practice: It was recommended among others that principal leaders in the colleges should foster an ethical environment in their institutions, by providing relevant ethics and soft skills training such as positivity, communication, delegation, problem-solving, and empathy. Again, principal leaders should prioritise creating an inclusive work environment where every tutor felt valued and respected. This involved actively promoting diversity, ensuring equal opportunities for growth, and addressing discrimination. It is believed that through this culture of respect, tutors are more likely to feel engaged, and motivated, thereby enhancing their overall quality of work life.